2023
DOI: 10.1002/adem.202201770
|View full text |Cite
|
Sign up to set email alerts
|

Large Refrigerant Capacity Induced by Table‐Like Magnetocaloric Effect in High‐Entropy Alloys TbDyHoEr

Abstract: Rare‐earth‐based high‐entropy alloys (HEAs) with large magnetocaloric effect (MCE) have been recently recognized as good candidates for magnetic refrigeration. Herein, the complex magnetic transition, MCE, refrigerant capacity (RC), and magnetic‐phase diagram of single‐phase TbDyHoEr HEA are studied. It is showed in the results that due to complex magnetic transition and an ideal table‐like MCE, the RC of TbDyHoEr is significantly improved from 883.19 to 1049.22 J kg−1 by melt‐spun treatment. In terms of RC va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…A number of materials have been investigated for magnetocaloric refrigeration across different temperature ranges. [57][58][59] For example, La(FeSi) 13 [60] displays a temperature change of 6.9 K at an operating temperature of 190 K, while Mn 3 GaC [61] exhibits a temperature variation of 4.5 K at 163 K, and Gd 2 Si 2 Ge 2 [62] has a temperature change of 4.9 K at 262 K under an applied magnetic field of 2 T. These materials exhibit the most significant temperature change at the phase-transition temperature, and their operating range and cooling capacity depend on the width and characteristics of their magnetic phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…A number of materials have been investigated for magnetocaloric refrigeration across different temperature ranges. [57][58][59] For example, La(FeSi) 13 [60] displays a temperature change of 6.9 K at an operating temperature of 190 K, while Mn 3 GaC [61] exhibits a temperature variation of 4.5 K at 163 K, and Gd 2 Si 2 Ge 2 [62] has a temperature change of 4.9 K at 262 K under an applied magnetic field of 2 T. These materials exhibit the most significant temperature change at the phase-transition temperature, and their operating range and cooling capacity depend on the width and characteristics of their magnetic phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…A change in sample temperature following an adiabatic change in the applied magnetic field is known as the magnetocaloric effect (MCE), which is an inherent feature of magnetic systems [32]. MCE has been extensively used in room and cryogenic temperature refrigeration applications [33,34]. In recent years, many experimental studies have found that the originally non-magnetic graphene can be made magnetic by doping magnetic transition metal atoms or through their replacement [35,36].…”
Section: Introductionmentioning
confidence: 99%